The effects of dentin and chemo-mechanical caries removal on the shear bond strength of dentin adhesive: An in vitro study - Nadia M AL-Shakir; Jabbar H Kamel (University of Mosul, College of Dentistry, 2006)
Aims: to measure the shear bond strength of composite restoration in vitro. Materials and Methods: The adhesion ability of dentin after chemomechanical method (Carisolv™) was measured compared to conventional one (bur) with the sound group which acts as a control. Three age groups (primary, young and old permanent teeth), in addition to two systems of adhesives (All Bond 2 and Optibond FL) were used. After the trimming and polishing of dentin surfaces to expose flat occlusal surfaces of the teeth, the carious lesion was removed by Carisolv™. Sixty teeth were used in this method, also 60 teeth were used in bur method, which are compared to 60 sound teeth. The composite resin was applied to the confined area of bonding measuring 3 mm in diameter, and two layers of composite core measuring 4 mm in height were applied to the rubbery mould. After thermocycling, the samples were stored in distilled water with crystals of thymol for 24 hours before testing. The interfaces between composites and dentin surfaces were loaded with a knife edge rod perpendicular to the long axis of the tooth by the Universal Testing Machine at across head of speed of 1mm/min., the load required to dislodge the restorations and modes of failure were recorded. Results: the primary teeth in sound group have the highest value of shear bond strength than Carisolv and bur treated surfaces with both dentin adhesives. Conclusion: Chemomechanical caries removal has no adverse effects on bonding to caries-affected dentin when modern bonding systems are used and old teeth dentin shows lower bond strength compared to young permanent teeth dentin.